International Cooperation in Achieving Environmental Security : Concepts, Mechanisms, and Governance - Al-Huraibi, Ahmed Yousuf; Al-Humaidi, Prof. Ahmed Qasim; Thabet, Huda Mohammed Ahmed (مجلة الشرق الأوسط للدراسات القانونية والفقهية, 2026)
This paper examines international cooperation in achieving environmental security — a subject of critical and growing urgency in the contemporary international order. Transboundary environmental threats, including climate change, biodiversity loss, and systemic pollution, have rendered unilateral national responses insufficient and have elevated environmental security to the forefront of global governance discourse. Drawing on a comprehensive review of legal instruments, institutional frameworks, and academic literature, the paper establishes a conceptual foundation for international cooperation and environmental security, analyses the principal legal mechanisms at both international and regional levels, and critically assesses the role of executive mechanisms including landmark global conferences and specialized international organizations. Particular attention is devoted to the case of Yemen, whose environmental predicament — compounded by a decade of armed conflict — represents an extreme manifestation of the governance failures this paper seeks to address. The paper argues that effective environmental security governance requires normative integration across branches of international law, robust financial and technical mechanisms, and genuine political will, underpinned by a coherent global institutional architecture.